The use of Platelet Rich Plasmain combination of guided tissue regeneration (chitosan) for bone defects: homogeneity analysis. - Dildar Abdullah Othman; Ziwar Ahmed Saleh; Raid Fahim Salman (Erbil Dental Journal)
Background and objective Guided bone regeneration is an accepted surgical procedure intended to increase the quantity and quality of host bone in localized defects of the alveolar bone. In this investigation, a novel combination by mixing of Platelet Rich Plasma (PRP) with the chitosan solution has been prepared. Method In method Platelet-rich plasma was prepared and mixed with chitosan in three different ratios (80:20, 90:10 and 95:5) the homogeneity status of the utilized samples has been studied using scanning electron microscopy (SEM), energy dispersive X-ray (EDS) analysis and FT-IR spectroscopy techniques. Results The result showed The homogeneity status of the utilized samples has been studied scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis and FT-IR spectroscopy techniques SEM Bigger cracks and obvious gaps can be seen clearly in the 20:80 ratio sample which shows the adhesion failure between PRP and chitosan in this mixture. By energy dispersive X-ray (EDX) It can be seen, that carbon percentages, which belong to chitosan, is a vital parameter that shows the optimum percentage for the formation of a homogeneous PRPchitosan compound and FTIR show the homogenous mixing without chemical changing of the mixture and showed the preservation of the chemical properties of each content. Conclusion The study concluded The homogeneity status of different ratios of novel material (mixture of PRP / Chitosan) revealed that 95:5 ratio was preferable to test for biocompatibility and bone regeneration.